Surface roughness, gloss and color change of different composites after exposure to ultimate challenges - Lemos, Cleidiel Aparecido Araujo [UNESP]; Mauro, Silvio José [UNESP]; Briso, André Luiz Fraga [UNESP]; de Souza, Fernanda de Carvalho Panzeri Pires; Navarro, Maria Fidela de Lima; Fagundes, Ticiane Cestari [UNESP] (Universidade Estadual de Campinas, 2018)
Aim: The study aimed to investigate the effect of the association of chemical and mechanical degradation on the surface roughness, gloss and color of nano and microfilled composites. Method: Disc-shaped specimens (n=10) were prepared for three nanocomposites (Filtek Z350XT, IPS Empress Direct, Charisma Diamond) and three microfilled composites (Estelite Σ Quick, Durafill VS, Renamel). After polishing, baseline surface roughness, gloss and color measurements were obtained. Specimens were submitted subsequently to the following challenges: chemical for 1 week (Hydrochloric acid, Coca-Cola and Red Wine) and mechanical (Toothbrushing). Surface roughness and gloss data were analyzed by Kruskal-Wallis followed by Dunn's test. Color difference (ΔE) was analyzed by one-way ANOVA and Tukey test. Results: The initial data were compared with those after challenges using the Wilcoxon test (p < 0.05). All composites showed a significant increase (p < 0.05) of surface roughness, after overstress. Filtek Z350 XT and Renamel had the lowest final surface roughness values and roughness increase (p < 0.05). The comparative analysis revealed that Estelite Σ Quick and Renamel did not significantly change the gloss after challenges (p=0.185). Filtek Z350 XT and IPS Empress Direct had higher color variations, after the challenges than the other resins (p < 0.05). Conclusion: Chemical and mechanical challenges influence on characteristics of all composites, except for gloss on Estelite Σ Quick and Renamel composites.
Keywords: Dental Resin; Immersion; Physical properties; Toothbrushing